ANALISIS TREND KINERJA KEUANGAN PERBANKAN SYARIAH TAHUN 2015 SAMPAI DENGAN 2017 - Veno, Andri; Syamsudin, Syamsudin (Universitas Islam Negeri Sunan Kudus, 2016)
Trend analysis is a method of statistical analysis that isintended to make an estimate or forecast the future. To do agood forecasting is needed various kinds of information (data)is quite a lot and observed in a period of relatively long , so thatthe analysis can determine how many big fluctuations and thefactors that influence those change . The profitability ratios willprovide an overview of the effectiveness of the management ofthe company. The greater the profitability means the better ,because the prosperity of the owner of the company increasedwith greater profitability. Profitability ratios consist of ProfitMargin, Basic Earning Power , Return on Assets and Return onEquity